DETERMINAN HARGA SAHAM PERUSAHAAN PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 : Untuk Mahasiswa UPN Veteran Jakarta - Sheila Sylvia, (2020)
This research is a quantitative study that aims to determine the determinants of conventional banking company stock prices listed on the Indonesia Stock Exchange (IDX). The dependent variable in this study is the stock price and the independent variables, namely liquidity, solvency, and profitability. The population in this study were all conventional banking companies in Indonesia, amounting to 41 companies. The sample selection in this study was carried out using apurposive sampling technique. The type of data in this study is secondary data and the analysis model in this study is panel data regression with the E-views program. The sample used in this study amounted to 24 conventional banking companies in the 2015-2019 period. The result of the panel data regression analysis testing using a significant level of 0.05 show that liquidity has no effect on stock prices, solvency has no effect on stock prices, and profitability has an effect on stock prices.